2016
DOI: 10.3797/scipharm.isp.2015.07
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-Lowering Effect of Beta Glucan Extracted from Saccharomyces cerevisiae in Rats

Abstract: Glucans are present in fungi, plants, algae, and bacteria. β-Glucan, one of the major cell wall components of Saccharomyces cerevisiae, has been found to enhance immune functions. Glucans are glucose polymers with an α- or β-type glycosidic chain. The role of (1→3)-β-D-glucan is in the maintenance of yeast cell wall shape and rigidity. Studies reveal that soluble glucans can lower total cholesterol and LDL levels in patients with hypercholesterolemia. The important benefit of β-glucan is to improve the immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 10 publications
0
18
0
1
Order By: Relevance
“…An additional study found that β-glucan treatment reduced the inflammation induced by a high cholesterol diet [ 35 ]. In a rat experimental model, β-glucan reduced total cholesterol, triglyceride, and malondialdehyde levels up to 42% [ 36 ]. In men, long-term clinical studies using soluble forms of β-glucans demonstrated decreased blood cholesterol in hypercholesterolemic patients [ 37 - 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…An additional study found that β-glucan treatment reduced the inflammation induced by a high cholesterol diet [ 35 ]. In a rat experimental model, β-glucan reduced total cholesterol, triglyceride, and malondialdehyde levels up to 42% [ 36 ]. In men, long-term clinical studies using soluble forms of β-glucans demonstrated decreased blood cholesterol in hypercholesterolemic patients [ 37 - 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lim et al [89] applied glucans from yeast-like fungus Aureobasidium pullulans to a hamster experimental animal model of hyperlipemia induced by a high-fat diet. In a rat experimental model, glucan reduced total cholesterol by 32% triglyceride by 64%, and malondialdehyde levels by 45% [90]. Moreover, in a study carried out by the current authors, yeast-derived glucan #300 markedly lowered total cholesterol levels in mice with experimentally-induced hypercholesterolemia [69].…”
Section: Beta Glucan As Food Supplementmentioning
confidence: 96%
“…The synthesis of bile acids occurs in the liver, in a series of reactions that convert hydrophobic cholesterol into a water-soluble compound, thus representing the primary pathway for cholesterol catabolism [ 59 , 60 ]. The formation of primary bile acids is primarily catalysed by the cytochrome P450 enzyme 7-α hydroxylase (CYP7A1) [ 61 ].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%